2015
DOI: 10.1371/journal.pone.0138215
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of GABA Equilibrium Potential by mGluRs in Rat Hippocampal CA1 Neurons

Abstract: The equilibrium potential for GABA-A receptor mediated currents (EGABA) in neonatal central neurons is set at a relatively depolarized level, which is suggested to be caused by a low expression of K+/Cl- co-transporter (KCC2) but a relatively high expression of Na+-K+-Cl- cotransporter (NKCC1). Theta-burst stimulation (TBS) in stratum radiatum induces a negative shift in EGABA in juvenile hippocampal CA1 pyramidal neurons. In the current study, the effects of TBS on EGABA in neonatal and juvenile hippocampal C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The value of E GABA , representing the polarizing state of GABAergic signaling, is controlled by both NKCC1 and KCC2 during the development and maturation of neurons (Lu et al, 1999 ; Ben-Ari et al, 2012 ). In cortical and hippocampal neurons, CCCs control the equilibrium potential ( E GABA ) of GABA A R-mediated current and consequently regulate the efficacy of GABAergic inhibition (Yang et al, 2015 ). NKCC1 and KCC2 are two important kinases in GABAergic signaling under both normal and pathophysiological conditions, such as epilepsy (Zhu et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…The value of E GABA , representing the polarizing state of GABAergic signaling, is controlled by both NKCC1 and KCC2 during the development and maturation of neurons (Lu et al, 1999 ; Ben-Ari et al, 2012 ). In cortical and hippocampal neurons, CCCs control the equilibrium potential ( E GABA ) of GABA A R-mediated current and consequently regulate the efficacy of GABAergic inhibition (Yang et al, 2015 ). NKCC1 and KCC2 are two important kinases in GABAergic signaling under both normal and pathophysiological conditions, such as epilepsy (Zhu et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…mGluR1 and mGluR5 are coupled to the stimulation of the phosphatidylinositol hydrolysis/calcium signal transduction, whereas the others are linked to the inhibition of the CAMP cascade (Hayashi et al, 1994). MCPG has been reported to be a non-specific antagonist of group I (mGluR1 and mGluR5) and group II receptors (mGluR2 and mGluR3) (Kohlmeier et al, 2013; Yang et al, 2015), exhibiting little effect on either the NMDA receptor or the AMPA/kainate receptor (Jane et al, 1993). Results in Figure 2 directly demonstrate that iGluRs may be involved in the glutamate-induced rise of calcium.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study using a theta-burst stimulation (TBS)-induced model reported that activation of metabotropic glutamate receptors (mGluRs) is involved in KCC2 in cortical neurons, leading to increased intracellular Ca 2+ ( 61 ). GABA A R may also be affected by the GluR5 kainate receptor after KA treatment.…”
Section: Discussionmentioning
confidence: 99%